Strategic Dynamism, Internal Capabilities and Firm Performance - Alessandro Arrighetti; Stefano Costa; Stefano De Santis; Fabio Landini (ZBW - Leibniz Information Centre for Economics, 2024)
The drivers of firm success in hyper-competitive markets have received growing attention by economic and management scholars. While earlier works paid particular attention to the analysis of firm strategic positioning in markets, most recent approaches emphasized the importance of internal capabilities. This paper combines these two views in a unified approach through a new conceptual construct, strategic dynamism, that we consider as “antecedent” of performance and “descendant” of capabilities. By using a large and unique survey carried out by the Italian Institute of Statistics we document that a) strategic dynamism explains performance differentials among firms, as captured by labor productivity growth and b) internal capabilities, measured as organizational and personnel capabilities, are important drivers of strategic dynamism. Managerial and policy implications are discussed.
Keywords: D21; D22; J24; 330; strategy; capabilities; performance; organizational capability; personnel capability